The determinants of caregiver use and its costs for elderly inpatients in Korea: a study applying Andersen's behavioral model of health care utilization and replacement cost method - Jennifer Ivy Kim; Sukil Kim (BMC, 2021)
Abstract Objectives The average annual healthcare expenditure among elderly patients in Korea is increasing rapidly in indirect healthcare sectors, requiring an understanding of factors related to the use of both formal and informal caregivers. This study analyzed the characteristics of caregiver use and caregiving costs among elderly patients hospitalized due to acute illness or exacerbation of chronic diseases. Methods A total of 819 study participants were selected from the 2017 Korea Health Panel Study Data. Replacement costing methods were applied to estimate the hours of informal caregiver assistance received by elderly inpatients. Elderly inpatients' predisposing, enabling, and need factors were studied to identify the relationship between caregiver uses, based on Andersen's behavior model. A two-part model was applied to analyze the factors related to care receipt and to estimate the incremental costs of care. Results Elderly inpatients who used tertiary hospitals (OR: 2.77, p-value < 0.00) and received financial support (OR: 2.68, p-value < 0.00) were more likely to receive support from a caregiver. However, elderly inpatients living alone were lesser to do so (OR: 0.49, p-value < 0.00). Elderly inpatients with Medicaid insurance (β:0.54, p-value = 0.02) or financial aid (β: 0.64, p-value < 0.00) had a statistically positive association with spending more on caregiving costs. Additionally, financial support receivers had incremental costs of $627 in caregiving costs than nonreceivers. Conclusions This study presented significant socioenvironmental characteristics of formal and informal caregiver use and the related expenditures. Healthcare management plans that encompass multiple social levels should be implemented to ease the caregiver burden. Trial registration Retrospectively registered.